2010
DOI: 10.1002/cne.22461
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular distribution of α1G subunit of T‐type calcium channel in the mouse dorsal lateral geniculate nucleus

Abstract: T-type calcium channels play a pivotal role in regulating neural membrane excitability in the nervous system. However, the precise subcellular distributions of T-type channel subunits and their implication for membrane excitability are not well understood. Here we investigated the subcellular distribution of the α1G subunit of the calcium channel which is expressed highly in the mouse dorsal lateral geniculate nucleus (dLGN). Light microscopic analysis demonstrated that dLGN exhibits intense immunoperoxidase r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
25
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 56 publications
7
25
0
Order By: Relevance
“…In line with previous rodent studies (Craig et al 1999;McKay et al 2006;Parajuli et al 2010;Perez-Reyes 2003;Talley et al 1999), our findings demonstrate that Ca v 3.1 immunoreactivity is strongly expressed throughout the monkey thalamus, with the exception of the reticular nucleus, which is known to be enriched in Ca v 3.3 (Liu et al 2011;Talley et al 1999). At the subcellular level, Ca v 3.1 immunostaining was found throughout the entire dendritic tree of thalamic projection neurons in normal and Parkinsonian monkeys.…”
Section: Subcellular Localization Of Ca V 31 In the Monkey Thalamussupporting
confidence: 91%
“…In line with previous rodent studies (Craig et al 1999;McKay et al 2006;Parajuli et al 2010;Perez-Reyes 2003;Talley et al 1999), our findings demonstrate that Ca v 3.1 immunoreactivity is strongly expressed throughout the monkey thalamus, with the exception of the reticular nucleus, which is known to be enriched in Ca v 3.3 (Liu et al 2011;Talley et al 1999). At the subcellular level, Ca v 3.1 immunostaining was found throughout the entire dendritic tree of thalamic projection neurons in normal and Parkinsonian monkeys.…”
Section: Subcellular Localization Of Ca V 31 In the Monkey Thalamussupporting
confidence: 91%
“…Approximately 95% of the immunogold particles were found to be located within 42 nm (mean ϩ 2 ϫ SD) of the cytoplasmic face of the membrane, and this distance was taken as the threshold for considering immunogold particles as being attached to the plasma membrane. This threshold distance is consistent with reports from earlier studies (Lörincz et al, 2002;Báldi et al, 2010;Parajuli et al, 2010).…”
Section: Methodssupporting
confidence: 82%
“…Animal anesthetization, fixation, and tissue processing for light microscopy (LM) and preembedding immunoelectron microscopy (EM) were performed as described previously (Kulik et al, 2004;Parajuli et al, 2010). Deeply anesthetized animals were transcardially perfused through the ascending aorta with 25 mM PBS, pH 7.4, for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…Although few data are already available concerning their precise localization in the various neuronal compartments, 48,49 calcium imaging technique, immunocytochemistry and electrophysiological recordings revealed that T-(R) calcium channels are not evenly distributed along dendrites. [50][51][52][53] For example, in CA1 pyramidal neurons where Ni 2C dependent synaptic plasticity mechanisms have been described at the Schaffer collateral synapses, 19,39 Ni 2C sensitive channels are more abundant in the distal area of the apical dendrites.…”
Section: Subcellular Localization Of T-type Channels and Synaptic Plamentioning
confidence: 99%